Effect of barrel temperature and feed moisture on the physical properties of chickpea, sorghum, and maize extrudates and the functionality of their resultant flours—Part 1. Issue 4 (1st April 2019) - Wang, Shuyang; Ai, Yongfeng; Hood‐Niefer, Shannon; Nickerson, Michael T.
Abstract: Background and objectives: The effect of barrel temperature (120 and 150°C, held constant in zones 4–6) and feed moisture (20 and 24%) on the physical properties of chickpea, sorghum, and maize extrudates and the functionality of their resultant flours was investigated. Findings: The moisture–temperature interaction significantly affected expansion ratio for all extrudates. In general, greater expansion occurred at 150°C; however, greater expansion occurred for chickpea and the cereal flours at high and low moisture levels, respectively. Expansion was negatively correlated with both hardness and bulk density. Extrusion also gelatinized starch, which was indirectly reflected by the 2–3× increase in water hydration capacity and 8‐40x decrease in pasting viscosities for all flours. Oil holding capacity remained relatively unchanged. Extrusion showed minor and mixed results on the emulsifying abilities of the flours, whereas all precooked flours were nonfoaming. The precooked flours also displayed reduced nitrogen solubility relative to the raw flours. Conclusions: Extrusion significantly affected the hydration and pasting properties of the flours. Maximum extrudate expansion required different extrusion conditions for chickpea flour as compared to cereal flours. Significance and novelty: Based on their functionality, the extruded flours have potential application in instant hot or cold beverages or may be blended with other flours to achieve the desired product functionality.